(untitled) - Tennick, Art (New York, 2010)
This solutions-based guide contains more than 200 DAX queries that can be immediately applied across a wide variety of BI-related problems. It begins with fundamental principles and simple queries and rapidly progresses to complex and sophisticated queries.
Keywords: Microsoft Excel (Tệp máy tính),Chương trình máy tính,Microsoft Excel (Computer file),Business intelligence; Computer programs